(Central) Auditory Processing: the impact of otitis media - Leticia Reis Borges; Jorge Rizzato Paschoal; Maria Francisca Colella-Santos (Clinics, 2013)
OBJECTIVE: To analyze auditory processing test results in children suffering from otitis media in their first five years of age, considering their age. Furthermore, to classify central auditory processing test findings regarding the hearing skills evaluated. METHODS: A total of 109 students between 8 and 12 years old were divided into three groups. The control group consisted of 40 students from public school without a history of otitis media. Experimental group I consisted of 39 students from public schools and experimental group II consisted of 30 students from private schools; students in both groups suffered from secretory otitis media in their first five years of age and underwent surgery for placement of bilateral ventilation tubes. The individuals underwent complete audiological evaluation and assessment by Auditory Processing tests. RESULTS: The left ear showed significantly worse performance when compared to the right ear in the dichotic digits test and pitch pattern sequence test. The students from the experimental groups showed worse performance when compared to the control group in the dichotic digits test and gaps-in-noise. Children from experimental group I had significantly lower results on the dichotic digits and gaps-in-noise tests compared with experimental group II. The hearing skills that were altered were temporal resolution and figure-ground perception. CONCLUSION: Children who suffered from secretory otitis media in their first five years and who underwent surgery for placement of bilateral ventilation tubes showed worse performance in auditory abilities, and children from public schools had worse results on auditory processing tests compared with students from private schools.